2014
DOI: 10.1590/s1517-83822014000400032
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Salmonella Typhi by loop-mediated isothermal amplification (LAMP) method

Abstract: An in-house loop-mediated isothermal amplification (LAMP) reaction was established and evaluated for sensitivity and specificity in detecting the presence of Salmonella Typhi (S. Typhi) isolates from Kelantan, Malaysia. Three sets of primers consisting of two outer and 4 inner were designed based on locus STBHUCCB_38510 of chaperone PapD of S. Typhi genes. The reaction was optimised using genomic DNA of S. Typhi ATCC7251 as the template. The products were visualised directly by colour changes of the reaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 18 publications
1
16
0
2
Order By: Relevance
“…The findings are similar with Tang et al, (2012), Zhang et al, (2012) and Wang and Wang et al, (2013) who reported the sensitivity of LAMP assay 10 times higher than the PCR-based method. The results are also in accordance with Abdullah et al, (2014) who reported that LAMP method was highly specific and 10 times more sensitive in detecting S. typhi as compared to the optimized conventional PCR method. However, Pavan Kumar et al, (2014) reported that the LAMP test developed for S. typhimurium was 100 times more sensitive than conventional PCR.…”
Section: Analysis Of Field Samplessupporting
confidence: 90%
“…The findings are similar with Tang et al, (2012), Zhang et al, (2012) and Wang and Wang et al, (2013) who reported the sensitivity of LAMP assay 10 times higher than the PCR-based method. The results are also in accordance with Abdullah et al, (2014) who reported that LAMP method was highly specific and 10 times more sensitive in detecting S. typhi as compared to the optimized conventional PCR method. However, Pavan Kumar et al, (2014) reported that the LAMP test developed for S. typhimurium was 100 times more sensitive than conventional PCR.…”
Section: Analysis Of Field Samplessupporting
confidence: 90%
“…In other studies, the sensitivity and specificity of Salmonella typhi detection with the use of three methods were compared: standard culturing method, conventional PCR and LAMP technology with the use of isothermal polymerase, which yielded 10 times greater sensitivity in the detection of these pathogens, compared to PCR [29].…”
Section: Resultsmentioning
confidence: 99%
“…This is true for typhoid fever also, where low bacterial count in the peripheral blood due to their intracellular existence in the reticulo endothelial system does not allow easy diagnosis by blood culture [ 2 , 18 ]. Recently loop-mediated isothermal DNA amplification (LAMP) assay has been introduced for typhoid diagnosis which is still under investiagtion [ 19 ].…”
Section: Discussionmentioning
confidence: 99%